Artificial Intelligence - Vorobeva, Darina (2022)
Vorobeva, D., El Fassi, Y., Pinto, D. C., Hildebrand, D., Mattila, A. S., & Herter, M. M. (2022). Artificial Intelligence: Service Employees Skills and Fear of Replacement [abstract]. In Proceedings of the European Marketing Academy Article 106728 European Marketing Academy (EMAC). https://proceedings.emac-online.org/pdfs/A2022-106728.pdf